Analisis Profesionalisme Pegawai dalam Pelayanan Wajib Pajak pada Kantor Badan Pengelolaan Pajak dan Retribusi Daerah Provinsi Sumatera Utara UPT PPD Sidikalang - Marihot Baktiar Purba; Heri Kusmanto; Warjio Warjio (Universitas Medan Area, 2022)
This study aims to determine and analyze the professionalism of employees and their obstacles in the service of taxpayers at the Office of the Regional Tax and Retribution Management Agency of North Sumatra Province UPT PPD Sidikalang. In order to answer and find solutions to problems, this research will use qualitative research methods. With this qualitative approach, the researcher went directly to the field to examine the object of his study and held direct interaction with the community aimed at obtaining in-depth information about the Analysis of Employee Professionalism in Licensing Services at the Office of the Regional Tax and Levy Management Agency of North Sumatra Province UPT PPD Sidikalang. The results of the study found that employees at the Office of the Regional Tax and Levy Management Agency of North Sumatra Province UPT PPD Sidikalang were still less professional in taxpayer services so they were less supportive of community activities. Factors constraining the professionalism of employees at the agency are employees at the agency doing more dominant work because they want to get a big income, taking the opportunity to commit violations if there is a possibility that their superiors don't know it, employees are not fully aware that the image of the agency is attached to each and most of the employees are not aware of it. willing to listen to public complaints outside of working hours, even though during working hours the employee also seems to be always busy so there is very little opportunity for the community to submit their complaints.